Application of the Talking Stick Learning Model to Improve Early Childhood Physical Motor Skills - Hadidja, Sitti; Herlina, Herlina; Bachtiar, Muhammad Yusri; Wahira, Wahira (International Journal of Multidisciplinary Approach Research and Science, 2025)
The Talking Stick learning model  is interpreted as a learning model for playing sticks, designed to measure the mastery of learning materials, foster learning motivation and create a fun learning atmosphere for students by using sticks. This research focuses on the Application of  the Talking Stick  Learning Model by Utilizing Used Goods to Improve Physicalmotor Skills in Early Childhood. The purpose of this study is to find out  the Application of the Talking Stick Learning Model by Utilizing Used Goods to Improve Children's Physicalmotor Skills after early childhood The type of research used is a type of qualitative research with a case study approach. The results of the study are as follows: 1) The Talking Stick  learning model is implemented in early childhood, where teachers provide direct guidance. The application of the talking stick learning model  is carried out in the process of activities that can improve children's oral language skills in the future As for the inhibiting factors in Talking Stick learning that "one of the disadvantages  of Talking Stick is that when students do not understand the lesson, then students will feel anxious and worried when Talking Stick in his hands. Meanwhile, the Supporting Factors are to test students' readiness in mastering the subject matter, practicing reading and understanding the subject matter quickly, according to the material that has been delivered and to be more active in learning because students never know that the stick will be their turn.